Financial Performance Evaluation using Financial Distress models with reference to Dabur India Ltd (Journal of Informatics Education and Research, 2024)
The global FMCG business is expected to reach close to $15000 billion by 2025 in the current era of e-commerce. Accordingly, FMCG is identified as the fourth-largest sector in India. One of the top businesses in India is Dabur India Ltd. As a result, we tried to evaluate the financial patterns and performance during the previous ten years. The main objective of this study is to assess the financial positions with respect to profitability, solvency, liquidity, etc. For the study, the ratio analysis techniques are employed and Financial Distress of Dabur India Ltd is analysed by Altman's Z-Score Model and Zmijewski Model. The study's overall conclusion unequivocally shows that Dabur is benefiting from positive financial performance across the board. This could assist Dabur India in maintaining a strong market share and a leading position in the FMCG industry.